(untitled) (American Journal of Applied Statistics and Economics, 2025)
The advent of the internet has led to increased cross-border interactions and transnational activities. Similarly, the increase in human capital investment has further given rise to digital migrants further highlighting the role of internet access in altering traditional migration dynamics. This study therefore examines the migration dynamics in West Africa using the Nigeria scenario. The dynamic OLS is used to analyze the data collected from various statistical bodies and agencies such as; the Nigeria CBN statistical bulletin as well as, the World Bank’s world development indicator databases. The data collected is from the period ranging from 2008 to 2023. Findings indicates that internet access and human capital investment both contributes negatively to migration dynamics in West Africa, as it significantly fuels the widespread emigration of skilled West Africa nationals. The insights gained in this work can inform evidence-based strategies to optimize the benefits and mitigate the risks associated with complex migration phenomenon. This increase in emigration has further exacerbated brain drain and human capital flight, meaning that West Africa countries would face significant challenges to its economic development, social cohesion, and long-term prosperity if migration issues are poorly managed. It is recommended that policy makers in collaboration with relevant agencies should, invest in expanding broadband infrastructure and ensuring affordable internet services with the view to using the technology to discourage brain drain and encourage digital migrant. It is further recommended that government should promote vocational and technical training programs aligned with domestic market needs with the view to encourage brain circulation.